FAKTOR-FAKTOR YANG DIPERTIMBANGKAN KONSUMEN MEMUTUSKAN MEMBELI DAN MENGGUNAKAN SMARTPHONE MEREK OPPO DI KECAMATAN PALU SELATAN - NDARI, TRIA WULAN (Fakultas Ekonomi Universitas Tadulako, 2015)
This study aims to determine factors that consumers consider in buying and using smartphones OPPO in South Palu Sub-district. The sampling technique is Accidental Side by selecting 105 people. The analytical tool is factor analysis. Based on the analysis of 21 indicators, the study finds factors that are considered by the consumers when deciding to buy and use a smartphone brand OPPO are: the first factors includes: promotion and price: X3 (Advertising media TV), X12 (promotions convincing), X14 (Prices are affordable), X15 (the physical form of interest), X17 (service center/customer service); the second factor is product quality that includes: X2 (friends suggestion), X6 (sophisticated feature), X10 (superior camera quality), X11 (good product quality), X21 (correspondence between price and quality); the third factor is lifestyle that includes: X1 (family suggestion), X16 (luxury product design), X19 (unique name and easy to remember), X20 (updated trend).